Christian metal : history, ideology, scene - Moberg, Marcus, 1978- (London ; New York : Bloomsbury Academic, 2015)
"Christian metal has always defined itself in contrast to its non-Christian, secular counterpart, yet it stands out from nearly all other forms of contemporary Christian music through its unreserved use of metal's main musical, visual, and aesthetic traits. Christian metal is a rare example of a direct combination between evangelical Christianity and an aggressive and highly controversial form of popular music and its culture. Christian Metal: History, Ideology, Scene is the first full exploration of the phenomenon of Christian metal music, its history, main characteristics, development, diversification, and key ideological traits from its formative years in the early 1980s to the present day. Marcus Moberg situates it in a wider international evangelical cultural environment, accounts for its diffusion on a transnational scale, and explores what religious meanings and functions Christian metal holds for its own musicians and followers. Engaging with wider debates on religion, media and popular culture, Christian Metal: History, Ideology and Scene is a much-needed resource in the study of religion and popular music"--Provided by publisher.
Christian metal : origins, definition and historical development -- Verbal, visual and Aasthetic traits -- The experiential, sensory and bodily dimension -- The contemporary transnational scene -- Main ideological and discursive traits -- Concluding remarks : Christian metal, alternative religious expression and identity.
Includes bibliographical references and index.
Keywords: Contemporary Christian music -- History and criticism; Heavy metal (Music) -- History and criticism